COST-UTILITY ANALYSIS PATIENTS WITH LOW BACK PAIN AFTER TREATMENT INTRAOSSEOUS BLOCKADES - M. V. Yakovlev; A. U. Kulikov; E. L. Sokov; I. E. Kornilova (Фармакоэкономика)
a total of 62 patients with a diagnosis of low back pain. Low back pain patients were randomized of two group. Patients of the first (main) group received a course of intraosseous blockades, while patients of the second (control group) received a course of conservatively treatment (analgetics, NSAIDs, myorelaxants, physical therapy). Measured direct costs at 1-year follow-up. Quality of life was measured with the Oswestry low back pain disability questionnaire, converted into utilities and transformed into quality-adjusted life years - QALY. The analysis will be performed for the health systems. Mean QALY in the first group was 0,358 and 0,134 in the second group.The cost-utility ratio for first group was 39 090,5 RUB for 1 QALY, and for standard therapy it was 179 552,2 RUB for 1 QALY. Treatment by intraosseous blockades is dominant alternative.